Messenger RNA Based Vaccines and Their immunological effect on diseases - Osama Mohammed Hasan (College of Pharmacy / Mustansiriyah University, 2022)
Because of its capabilities for fast development, potency, secure delivery, and promise for   cost effective manufacture, mRNA vaccines are a promising vaccination technique. Many recent research has suggested that mRNA vaccines could be effective intreating a wide range of tumor and viral disorders where standard vaccine techniques have failed to stimulate protective immune responses. The inefficient and unstable in vivo distribution of mRNA has limited their application. Direct electroporation of mRNA vaccines into dendritic cells induced the generation of protective antibodies capable of destroying infected or transformed cells and inducing polyclonal CD8+ and CD4+ that mediated Ag specific T cell responses. in this review mRNA vaccines in detail were examined, as well as future objectives and challenges in the prevention of infectious diseases